2018
DOI: 10.1186/s12910-018-0338-6
|View full text |Cite
|
Sign up to set email alerts
|

African bioethics: methodological doubts and insights

Abstract: BackgroundA trend called ‘African bioethics’ is growing on the continent due to perceptions of existing bioethics, especially guidelines for international collaborative research, as ‘ethical imperialism’. As a potential alternative to ‘Western Principlism,’ ‘African bioethics’ is supposed to be indigenous to Africa and reflective of African identity. However, despite many positive insights in the on-going discussions, it is feared that the growth of bioethics in Africa lacks a clear direction. Some of the view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 19 publications
(43 reference statements)
0
21
0
1
Order By: Relevance
“…Finally, further exploration of the extent to which community values across various parts of Africa align with international principles of research ethics is encouraged. This work could help to ground the ongoing largely theoretical debate on the need for a distinct "African Bioethics" (Barugahare, 2018).…”
Section: Research Agendamentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, further exploration of the extent to which community values across various parts of Africa align with international principles of research ethics is encouraged. This work could help to ground the ongoing largely theoretical debate on the need for a distinct "African Bioethics" (Barugahare, 2018).…”
Section: Research Agendamentioning
confidence: 99%
“…For example, Ssebunnya (2017) suggested that "rather than pursuing a distinct African bioethics, African bioethicists and philosophers would do well to elucidate the universalizability of communitarian traditional African thought-and thus enrich the content-thin concept of the common morality-for the benefit of bioethics as a whole" (p. 30). Barugahare has also argued that thoughtful analysis should be provided to determine how well suited existing international principles of ethics are to the African context, suggesting that merely a superficial focus on how they were generated is short-sighted (Barugahare, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…De ahí que, en algunos ambientes universitarios, ante la percepción de un creciente colonialismo ético, esté surgiendo con fuerza la necesidad de implementar una bioética africana, que ponga su foco en las necesidades y conflictos propios, y que emerja, a la vez, como alternativa potencial al modelo principialista occidental (Barugahare, 2018).…”
Section: éTica Para La Implantación De Cuidados Paliativos Pediátricosunclassified
“…Yet, this is a principle that has been widely challenged in other areas of research as not being representative of more communitarian values, such as those held by many cultures across Africa. 49,50 In such contexts, community-oriented decision-making processes may in fact be promoted and valued, rather than individualistic ones. This is a case of a principle and its associated values being deemed important from an ll OPEN ACCESS imported context, where in fact critical reflection and application is required.…”
Section: Diverse Values: Ensuring Inclusivity At All Levelsmentioning
confidence: 99%